Solve for t 6-3t=-18

Math
6-3t=-18
Move all terms not containing t to the right side of the equation.
Tap for more steps…
Subtract 6 from both sides of the equation.
-3t=-18-6
Subtract 6 from -18.
-3t=-24
-3t=-24
Divide each term by -3 and simplify.
Tap for more steps…
Divide each term in -3t=-24 by -3.
-3t-3=-24-3
Cancel the common factor of -3.
Tap for more steps…
Cancel the common factor.
-3t-3=-24-3
Divide t by 1.
t=-24-3
t=-24-3
Divide -24 by -3.
t=8
t=8
Solve for t 6-3t=-18

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top